Testing the asymmetric effects of exchange rate pass-through in BRICS countries: Does the state of the economy matter? - Balcilar, Mehmet; Roubaud, David; Usman, Ojonugwa; Wohar, Mark E. (Wiley, 2021)
This paper investigates not only the question of whether there is exchange rate pass-through (ERPT) but also the extent to which the pass-through is asymmetric or state-dependent in the BRICS countries. Using monthly data from 1999:M1 to 2019:M12 and non-linear smooth transition vector autoregressive (STVAR) model, our results provide evidence of period-specific ERPT between the upper and lower regime periods, governed by the selected transition variables. The results further suggest that the pass-through of exchange rate is higher when the economy is experiencing large appreciations and expansions as well as large depreciations and recessions. Theimplication for these findings is that ERPT is strongly affected by the state of the economy.
Keywords: BRICS countries; exchange rate pass-through; inflation; smooth transition vector autoregressive